Strategic tool to estimate the consumption patterns of non-residents spectators at sporting events (Liga NOS): Adaptation to Portuguese reality - Gonçalo Quintal (FUCAPE Business School, 2016)
The purpose of this study was to adapt the questionnaire of Preuss, Seguin and O’Reilly (2007) to Portuguese reality to analyse the phenomenon of consumption patterns of non-residents spectators at sporting events. For this, an exploratory study was conducted to check its psychometric properties when applied to Portuguese reality. For the sample, 58 non-resident spectators were randomly selected in the match between Futebol Clube Paços de Ferreira and Sporting Clube de Portugal of 19th round of Liga NOS in the city of Paços de Ferreira. Data analysis was based on descriptive statistics and Cronbach’s alpha reliability test. The results suggest acceptable values for internal consistency and reliability. As main conclusions, the adapted version can be used to analyse the profile and consumption patterns of non-residents spectators, which will help to define marketing strategies more effective and efficient for clubs and host cities, thus contributing to improving offer and more quality in the services provided for spectators of such events.